Exercising the Right Side of the Brain Might Help Protect Against Alzheimer's Disease - Dockree, Paul; Brosnan, Méadhbh B.; Robertson, Ian H.; Wiegand, Iris (My University, 2018)
Alzheimer’s disease is a condition that affects the brain, changes the way people act and behave, and makes it difficult for them to remember. Lots of research has shown that older adults who get more brain exercise are better able to fight this disease. Why does brain exercise protect against Alzheimer’s disease? One hypothesis (idea) is that brain exercise makes the right hemisphere (side) of the brain stronger, and this stronger right hemisphere helps protect people against Alzheimer’s disease. We ran a study to test this. Older adults performed a computer task which allowed us to check whether the right side of the brain was stronger than the left side. We found that people who get more brain exercise had stronger right hemispheres.
PUBLISHED
Keywords: Alzheimer's disease; Exercise